Pemanfaatan Metode TOPSIS untuk Menentukan Kualitas Minyak pada Buah Sawit - Hasugian, Abdul Halim; Irawan, Muhammad Arief (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
This research discusses the utilization of the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method to determine the quality of oil in palm fruits. The palm oil industry is an important economic sector for Indonesia, significantly contributing to national income and the welfare of farmers. The quality of oil produced from palm fruits is a crucial factor affecting palm oil production. The TOPSIS method is used in this study because of its ability to synthesize various factors influencing oil quality, including moisture content, oil content, and the percentage of loose fruits. This method allows researchers to rank and evaluate oil quality based on its proximity to the ideal solution. In this study, each quality factor is weighted and analyzed to determine the palm fruits with the best oil quality. The results of applying the TOPSIS method in this study show that the use of this method is effective in identifying the optimal quality of palm fruit oil based on relevant criteria. The information generated from this research can provide valuable insights for palm oil farmers and producers. Additionally, the application of the TOPSIS method helps stakeholders optimize harvest time to enhance oil quality optimally and provides further understanding of the correlation between the quality of palm fruit oil and the resulting palm oil quality.